A new framework for interleaved scanning in cardiovascular MR: Application to image‐based respiratory motion correction in coronary MR angiography. Issue 2 (17th March 2014) - Henningsson, Markus; Mens, Giel; Koken, Peter; Smink, Jouke; Botnar, Rene M.
<x xml:space="preserve">Abstract</x> Purpose To describe a new framework for interleaving scans and demonstrate its usefulness for image‐based respiratory motion correction in whole heart coronary MR angiography (CMRA). Methods Scan interleaving using the proposed approach was achieved by switching between separately defined, independent scans at arbitrary time points during their execution, using a generic function call. The scan interleaving framework was used to perform scan interleaving for image‐based respiratory navigation of CMRA with spiral, radial, and Cartesian echo‐planar imaging (EPI) navigator k‐space trajectories. Eight healthy volunteers were scanned. Results Improved coronary vessel sharpness and visual scores were obtained using spiral and Cartesian EPI navigators compared with radial navigators. Conclusion The usefulness of the proposed scan interleaving framework was demonstrated for image‐based respiratory motion correction. It facilitated more direct comparisons of image navigator acquisitions with different k‐space trajectories. Furthermore, we could demonstrate that spiral and Cartesian EPI navigators may be particularly suitable for image‐based motion correction, as they provide improved motion correction and high navigator apparent signal‐to‐noise ratio while spending very little magnetization, thereby minimizing saturation effects. Magn Reson Med 73:692–696, 2015. © 2014 Wiley Periodicals, Inc.